Genetic Characterization of Staphylococcus aureus From Subclinical Mastitis Cases in Dairy Cows in Rwanda - Ndahetuye, Jean Baptiste; Leijon, Mikael; Båge, Renée; Artursson, Karin; Persson, Ylva (Frontiers in Veterinary Science, 2021)
Whole-genome sequencing was carried out on 30 Staphylococcus (S.) aureus isolates from dairy cows with subclinical mastitis from all five provinces of Rwanda. Twenty-five of the isolates produced enough sequence to be analyzed using core genome multilocus sequence typing (cg-MLST). The isolates group into three main clusters. The largest cluster contain isolates of sequence type (ST) 152 (n = 6) and the closely related ST1633 (n = 2). These sequence types have previously mainly been encountered in humans. The isolates of the second-largest cluster belong to ST5477 (n = 5),so far exclusively isolated from cows in Rwanda. The third cluster consists of isolates of ST97 (n = 4), which is a well-known bovine-adapted sequence type. These three clusters were all widespread over the country. Isolates of the usually human-adapted sequence types 1 (n = 2) and 5 (n= 1) were found and a single isolate of ST2430, previously found among humans in Africa. Finally, four isolates of novel sequence types were found: ST7108 (n = 2), ST7109 (n = 1), and ST7110 (n = 1). The blaZ penicillin resistance gene was found in 84% of the isolates and was in all cases corroborated by phenotypic resistance determination. Five (20%) of the isolates carried a tetracycline resistance gene, tet(K) or tetM, and three of these five also displayed phenotypic resistance while two isolates carried a tetM-gene but were yet tetracycline susceptible. Seven (28%) isolates carried the dfrG gene conferring resistance to trimethoprim. Four of these isolates indeed were resistant to trimethoprim while three isolates were sensitive. The str gene conferring resistance to aminoglycosides was found in three isolates; however, none of these displayed resistance to gentamycin. Our data revealed a high diversity of the sequence types of S. aureus isolates from cows with subclinical mastitis in Rwanda. Two major clusters of ST97 and ST5477 are likely to be bovine adapted and cause mastitis while the third cluster of ST152 usually have been found in humans and may signify a recent transmission of these types from human to cows, for example from hand milking. The high prevalence of this sequence type among dairy cows may pose zoonotic threat. The sequence types were widely distributed without any geographic correlation. Penicillin resistance, the most common type of resistance with a prevalence over 80%, but also tetracycline and trimethoprim resistance were displayed by several isolates.